The Role of Women in Cacao Farming in Calinan, Davao City, Philippines: An Empirical Investigation - Obsioma, Sarah Jane P.; Sarmiento, Jon Marx P.; Aguinaldo, Roxanne T.; Acuna, Thaddeus R.; Fuentes, Anne Shangrila Y. (Review of Women's Studies; Vol 24 No 1-2 (2014): Review of Women's Studies Volume XXIV, Numbers 1-2 (January-December 2014), 2023)
Cacao (Theobroma cacao L.), a perennial cash crop cultivated in humid tropics, has high and stable demand for cacao beans as raw materials in chocolate production both locally and internationally. Around 9,584 hectares of land are planted with cacao in the Philippines with Davao City contributing 1,332 hectares. The goal of this study is to identify the role of women in cacao farming. A sample of 32 farmers with 13 women farmers in the village of Subasta, Calinan, Davao City was used in the empirical investigation focusing on the productivity, technical efficiency and profitability performance. Women in cacao farming could take the role of farmer, wife of the farmer or as farm laborer. On average, female farmers were as productive, efficient and profitable as their male counterparts. They produced 2,989 kg of wet beans per hectare earning PhP 46,985 annually. Around 53% of the wives contributed to farming operations, 68% in farm decisions and 74% had financial contributions. Some 12% of the women were hired as farm laborer. Farm tasks for women laborer and wives include farm cleaning, weeding, harvesting, pod sleeving, pod breaking and drying of beans. The farmers' cooperative pays 2 pesos/kg for tasks including weighing, pouring of beans to the fermentation boxes, transferring beans to the solar dryer, sacking and transferring of beans to the storage area while female laborers are paid 1 peso/kg for sorting and grading of beans. This study concludes that cacao farming can also be the realm of female farmers, however, some gender differences were noted related to farm tasks and wage rate.